Implementation of an AC model for transmission expansion planning considering reliability constraints - Mahmoudabadi, Amin; Rashidinejad, Masoud; Zeinaddini-Meymand, Majid; Rahmani, Mohsen [UNESP] (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2013)
In this paper, a hybrid heuristic methodology that employs fuzzy logic for solving the AC transmission network expansion planning (AC-TEP) problem is presented. An enhanced constructive heuristic algorithm aimed at obtaining a significant quality solution for such complicated problems considering contingency is proposed. In order to indicate the severity of the contingency, 2 performance indices, namely the line flow performance index and voltage performance index, are calculated. An interior point method is applied as a nonlinear programming solver to handle such nonconvex optimization problems, while the objective function includes the costs of the new transmission lines as well as the real power losses. The performance of the proposed method is examined by applying it to the well-known Garver system for different cases. The simulation studies and result analysis demonstrate that the proposed method provides a promising way to find an optimal plan. Obtaining the best quality solution shows the capability and the viability of the proposed algorithm in AC-TEP. © Tübi̇tak..
Keywords: Fuzzy decision making; Hybrid heuristic algorithm; Nonconvex optimization; Reliability; Transmission expansion planning; Constructive heuristic algorithm; Fuzzy Decision making; Hybrid heuristic algorithms; Nonconvex optimization problem; Reliability constraints; Voltage performance indices; Fuzzy logic; Heuristic algorithms; Optimization; Nonlinear programming